Exploring Integrated Vocabulary and Speaking Learning in “Spoken English Vocabulary and Corpus” Class - Riskina, Aulia; Rafidiyah, Dina; Nurfauziah, Dwi Hana; Dayanti, Gista Rahma; Aflahah, Noor Aida; Amalin, Khusnul; Andreas, Rino; Saputro, Duwi (Jurnal Keilmuan dan Keislaman, 2023)
This article explores the strategy of integrating vocabulary and speaking learning in spoken English classes and investigates how lecturers teach these skills. The integration of vocabulary and speaking is essential as speaking is a productive skill that requires input (vocabulary) and output (spoken English). This study aims to delve into how this integration enhances speaking skills by providing language exposure through contextually relevant vocabulary usage. The lecturer's approach involves situational learning videos, focusing on pronunciation and contextual understanding. Moreover, the incorporation of corpus data, depicting vocabulary usage in various speaking contexts, aids students in practicing vocabulary in appropriate situations. The results showcase a spectrum of student responses, ranging from natural speakers to those reliant on scripted preparation. Assignments, including role-plays and conversational scenarios, foster vocabulary utilization in congruent contexts. Student interviews reflect improved understanding of spoken English through vocabulary exploration strategies, facilitating comprehension and communication. The study concludes that integrating vocabulary and speaking learning enhances spoken English proficiency, guiding educators to develop more effective teaching methodologies. Future research recommendations include expanding participant numbers for richer data insights.